Hypoxia‐induced PGK1 expression promotes esophageal squamous cell carcinoma progression via stimulating MYH9‐mediated GSK3β/β‐catenin signalling - Jia‐cheng Xu; Lin‐feng Wu; Tian‐yin Chen; Yan‐bo Liu; Yi‐fei Zhang; Ping‐hong Zhou; Yi‐qun Zhang (Clinical and Translational Medicine)
Abstract Background Phosphoglycerate kinase 1 (PGK1) serves as a critical metabolic enzyme in the process of glycolysis and has many nonmetabolic functions in tumour progression. One of the most prevalent malignant tumours is still esophageal squamous cell carcinoma (ESCC), with high recurrence rates, high probabilities of metastasis, and poor prognoses. However, the molecular mechanisms and physiological contribution of PGK1 to ESCC carcinogenesis remain largely elusive. Methods Esophageal cancer bioinformatics analysis and tissue microarray analysis were employed to elucidate the aberrant expression of PGK1 during ESCC progression. The carcinogenic effect of PGK1 was examined using cell proliferation, migration and sphere formation assays. Mass spectrometry analysis, immunoprecipitation, ChIP and luciferase assays, hypoxia assays and in vitro and in vivo experiments were used to clarify the mechanism of the PGK1‒MYH9 interaction in the β‐catenin/c‐Myc signalling pathway. Results We clarified that in patients with ESCC, elevated PGK1 levels were linked to poor survival, tumour size, lymph node metastatic status, and TNM stage. In vivo and in vitro experimental analyses revealed that PGK1 promoted ESCC cell tumour stemness and EMT both in vivo and in vitro. Mechanistically, we discovered that PGK1 interacts with myosin‐9 (MYH9), leading to MYH9‐mediated ubiquitination‐mediated degradation of GSK‐3β, thereby triggering the β‐catenin signalling pathway and transcriptionally increasing c‐Myc expression. In addition, we found that hypoxic conditions upregulated PGK1, with HIF‐1α transactivating PGK1 expression, further promoting the PGK1‐MYH9 interaction and PGK1/MYH9/β‐catenin/c‐Myc axis activation. Conclusions PGK1 promotes ESCC tumourigenicity and migratory capacity by facilitating β‐catenin‐dependent c‐Myc transcription. Under hypoxic conditions, the PGK1‒MYH9 interaction is strengthened, and HIF‐1α‐mediated transcription increases PGK1 expression, thereby activating the β‐catenin/c‐Myc signalling pathway. Taken together, PGK1 holds promise as a potential biomarker for predicting postoperative prognosis and recurrence in patients with ESCC.